Boundary element simulation of void formation in fibrous reinforcements based on the Stokes–Darcy formulation - Patiño Arcila, Iván David; Power, Henry; Nieto Londoño, César; Flórez Escobar, Whady Felipe (Elsevier, 2016)
The Boundary Element Method (BEM) is applied for the solution of the problem of void formation in fibrous reinforcements used in composite materials. Stokes and Darcy formulations for the channel and porous medium are considered, including three main differences with most of the previous models reported in the literature that deal with this type of problem: the consideration of the general form of the Beavers–Joseph slip condition instead of the Saffman simplification, the calculation of the flow direction-dependent capillary pressure in the porous medium without experimental factors and the consideration of the surface traction effects in the channel fluid front. An analytical solution of a simple problem is presented to assess the accuracy and convergence of the BEM solution, obtaining good agreement between the results.